2021
DOI: 10.3389/fonc.2021.646267
|View full text |Cite
|
Sign up to set email alerts
|

Exploring MRI Characteristics of Brain Diffuse Midline Gliomas With the H3 K27M Mutation Using Radiomics

Abstract: ObjectivesTo explore the magnetic resonance imaging (MRI) characteristics of brain diffuse midline gliomas with the H3 K27M mutation (DMG-M) using radiomics.Materials and MethodsThirty patients with diffuse midline gliomas, including 16 with the H3 K27M mutant and 14 with wild type tumors, were retrospectively included in this study. A total of 272 radiomic features were initially extracted from MR images of each tumor. Principal component analysis, univariate analysis, and three other feature selection method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
(49 reference statements)
0
18
0
1
Order By: Relevance
“…Historically, MR images have been primarily used for a qualitative and objective assessment of the tumor by clinicians. However, recent neuroimaging advances have contributed to the development of quantitative and molecular MRI techniques (17)(18)(19), which have the potential to transform the interpretation and application of imaging results into routine clinical practice. Nonetheless, research into fully quantitative MRIbased biomarkers of glioma is still very much an ongoing endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, MR images have been primarily used for a qualitative and objective assessment of the tumor by clinicians. However, recent neuroimaging advances have contributed to the development of quantitative and molecular MRI techniques (17)(18)(19), which have the potential to transform the interpretation and application of imaging results into routine clinical practice. Nonetheless, research into fully quantitative MRIbased biomarkers of glioma is still very much an ongoing endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…The model had an AUC of 0.791 in the training set and 0.737 in the test set, and the AC of the model was 73% in the test set. Furthermore, Li et al ( 34 ) explored visually accessible MRI features of 30 patients with DMGs with and without the H3 K27M mutation using principal component analysis based on radiomics and found that T2w sequences may be more valuable and that cystic formation may be a biomarker for diagnosing DMGs with an H3 K27M mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies assessed MRI appearances, with or without CT. Two series (one publication each for H3 K27-altered and H3 G34-mutant gliomas) assessed PET (positron emission tomography) using the amino acid tracer FET (fluorine-18-fluoroethyl-L-tyrosine) [13,15]. Three recent papers assessed the use of MRI radiomics for predicting H3 K27 status [38,46,47].…”
Section: Data Synthesismentioning
confidence: 99%
“…There were notable differences in tumor location depending on the age group studied. The thalami were the most common location in cohorts which either largely or exclusively assessed adult patients [22,25,28,46,48]. In contrast, the brainstem was the most common overall location in studies targeting a pediatric population [10,13,31,51].…”
Section: Tumor Locationmentioning
confidence: 99%